Respuesta :

Answer:

B. y = 2x - 2

E. [tex] y + 4 = 2(x + 1) [/tex]

F. [tex] y - 6 = 2(x - 4) [/tex]

Step-by-step explanation:

The equation of the line can be found using either the point-slope equation or the slope-intercept equation.

✔️Equation of the line in point-slope using the slope and the coordinates of the point (4, 6):

Slope = m = change in y/change in x

Using (4, 6) and (-1, -4),

m = (-4 - 6)/(-1 - 4)

m = -10/-5

m = 2

Substitute m = 2, and (a, b) = (4, 6) into the point-slope equation form [tex] y - b = m(x - a) [/tex]

Thus:

[tex] y - 6 = 2(x - 4) [/tex]

✔️Equation of the line in point-slope using the slope and the coordinates of the point (-1, -4):

Slope = m = 2

Substitute m = 2, and (a, b) = (-1, -4) into the point-slope equation form [tex] y - b = m(x - a) [/tex]

Thus:

[tex] y - (-4) = 2(x - (-1)) [/tex]

[tex] y + 4 = 2(x + 1) [/tex]

✔️Equation of the line in slope-intercept form, y = mx + b

Where,

m = slope = 2

b = y-intercept = -2 (the point where the line intercepts the y-axis)

Thus, substitute m = 2 and b = -2 into y = mx + b

y = 2x + (-2)

y = 2x - 2